Percutaneous microwave ablation for hepatic cavernous hemangiomas: a preliminary clinical result - Cheng, Zhigang; Liang, Ping; Yu, Xiaoling; Han, Zhiyu; Zhou, Pei; Liu, Fangyi; Yu, Jie (European Journal of Oncology and Environmental Health, 2015)
Purpose: To explore the clinical application value of microwave (MW) ablation treatment for hepatic cavernous hemangiomas (HCHs) under percutaneous ultrasound (US) guidance. Methods: From July 2006 to January 2011, 14 patients (9 female and 5 male) with 18 HCHs (mean maximum diameter, 36.6±26.1 mm) were treated by MW ablation under US-guidance percutaneously. The diagnoses of HCHs were proven pathologically in 78.6% (11/14) patients by US-guided core needle biopsy prior to ablation. The other 3 cases refused biopsy and had their diagnoses confirmed by typical presentations on contrast-enhanced imaging. Four inclusion criteria including symptoms related to HCH were recommended. The follow-up period was 22.7±16.0 months. Results: Average ablation MW energy and emission time were 55.2±53.3 kJ (range 13.5 to 207 kJ) and 1021.3±886.4 s (range 270 to 3450 seconds) for each lesion, respectively. Fifteen nodules (83.3%) were completely treated and no evidence of recurrence was found on contrast enhanced imaging during follow-up. The three large HCHs (16.7%) were partially ablated as being adjacent to the gastrointestinal tracts or an important hepatic hilum structure. After ablation, three patients’ symptoms relating to HCHs were alleviated in differing degrees. No severe complications occurred in the peri-operation or follow-up periods. Minor complications mainly included fever, local pain and abnormal hepatic function. Conclusion: US-guided percutaneous MW ablation is a safe, feasible and effective treatment for selected patients with HCHs and can be considered as a minimally invasive alternative to surgical resection.